Uncertain Demand, Consumer Loss Aversion, and Flat-Rate Tariffs - Fabian Herweg (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
The so called flat-rate bias is a well documented phenomenon caused by consumers' desire to be insured against fluctuations in their billing amounts. This paper shows that expectation-based loss aversion provides a formal explanation for this bias. We solve for the optimal two-part tariff when contracting with loss-averse consumers who are uncertain about their demand. The optimal tariff is a flat rate if marginal cost of production is low compared to a consumer's degree of loss aversion and if there is enough variation in the consumer's demand. Moreover, if consumers differ with respect to the degree of loss aversion, firms' optimal menu of tariffs typically comprises a flat-rate contract.
Keywords: D11; D43; L11; 330; Consumer Loss Aversion; Flat-Rate Tariffs; Nonlinear Pricing; Uncertain Demand; Betriebliche Preispolitik; Preisdifferenzierung; Konsumentenverhalten; Risikoaversion; Nachfrage; Risiko; Theorie